The End of the Limia-Seixas Couple: the Marriage Annulment Sentence of Xoana Vázquez das Seixas and Fernán Eanes de Limia - García-Fernández, Miguel; Pichel, Ricardo (Madrygal. Revista de Estudios Gallegos, 2023)
The marriage between Xoana Vázquez das Seixas and Fernán Eanes de Limia had a notable role in the Galician nobiliary panorama of the late 14th century, as well as standing out in the cultural sphere because their names appear in a prominent place of the chronistic set that makes up the so-called Crónica geral galega (BNE Ms. 8817), which shows their role in the dynamics of possession and circulation of Galician medieval prose texts in the manorial courts. However, until now, nothing was known about the end of this marriage, which was not motivated by the death of either of the spouses but by a marriage annulment sentence granted in 1398 and whose edition is offered for the first time in this work.